2010
DOI: 10.1116/1.3466811
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of submicron-sized features in InP/InGaAsP/AlGaInAs quantum well heterostructures by optimized inductively coupled plasma etching with Cl2/Ar/N2 chemistry

Abstract: Inductively coupled plasma dry etching for the fabrication of fine-pitch patterns in a wide range of InP-based materials has been developed. The effect of plasma chemistry (the N2 content in the total Cl2/Ar/N2 gas mixture) on the degree of undercut in the sidewall profile and surface morphology has been studied. Optimization of the etch process conditions produces strong passivation effects on the sidewalls, together with a highly anisotropic process, while still maintaining a good etch rate (560–730 nm/min).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…A dry-etching process that can produce highly anisotropic profiles, smooth sidewalls, and a smooth etched surface is generally required to fabricate optical waveguides or cavities with minimal optical loss. Inductively coupled plasma (ICP) etching has been widely used in the past for fabricating such InP-based optical devices, and various chlorine- [1][2][3][4][5][6] and HBr-containing [7][8][9] chemistries have been proposed for anisotropic ICP etching of InP. However, the influence of the etched surface composition upon the passivation mechanism is often unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A dry-etching process that can produce highly anisotropic profiles, smooth sidewalls, and a smooth etched surface is generally required to fabricate optical waveguides or cavities with minimal optical loss. Inductively coupled plasma (ICP) etching has been widely used in the past for fabricating such InP-based optical devices, and various chlorine- [1][2][3][4][5][6] and HBr-containing [7][8][9] chemistries have been proposed for anisotropic ICP etching of InP. However, the influence of the etched surface composition upon the passivation mechanism is often unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The resist exhibits good selectivity against plasma etching and could be utilized in our fabrication. Excellent plasma etching profile of InPbased material has also been demonstrated before [24][25], and it could act as an important reference in our fabrication. Since the height of our structure is only about 200 nm, the etching process is much straightforward, where recipe without chlorine can be used.…”
Section: Other Considerationsmentioning
confidence: 85%
“…In our InP etching model, atomic nitrogen N is introduced as a neutral species yielding to the passivation reactions along the etched surface. Indeed, previous experimental works have shown the passivating role of N 2 used in InP etching under chlorine‐based plasma 3, 4, 17, 19, 35. Lee et al4 showed that for %N 2 lesser than 30%, the isotropic etching was observed in PhC hole while for 60%N 2 , the anisotropy of PhC patterns was improved but with rough sidewalls on the bottom of holes.…”
Section: Inp Etching Simulatormentioning
confidence: 99%
“…The optical performances of such components are tributary to the good control of the etched structure anisotropy. Over the last years, a variety of plasma chemistry using high density plasma–reactive ion etching (HDP‐RIE) is performed for a high aspect ratio InP etching with a smooth sidewall surface and without local defects like undercut, bowing, and trenching 1, 3–6. CH 4 /H 2 ,7–9 Cl 2 ,10, 11 Cl 2 /Ar,12 BCl 3 /Cl 2 ,13 HBr,14, 15 and SiCl 4 1, 16 have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation